A serosurvey for selected pathogens in Greek European wild boar. Issue 2 (28th August 2015) - Touloudi, A.; Valiakos, G.; Athanasiou, L. V.; Birtsas, P.; Giannakopoulos, A.; Papaspyropoulos, K.; Kalaitzis, C.; Sokos, C.; Tsokana, C. N.; Spyrou, V.; Petrovska, L.; Billinis, C.
Abstract : Objectives: Serum samples, collected from 94 European wild boar ( Sus scrofa ) during the hunting seasons 2006 ‐2010 from different regions of Greece, were examined in order to estimate the role of these wildlife species as reservoir of pathogens important for livestock and/or public health. Materials and Methods: The assays used for this purpose were commercial indirect ELISA for the detection of antibodies against porcine circovirus type 2 (PCV‐2), porcine reproductive and respiratory syndrome (virus) (PRRSV), Aujeszky's disease virus (ADV), influenza A (IA) virus, Actinobacillus pleuropneumoniae, Mycoplasma hyopneumoniae, Salmonella species, Trichinella species and indirect immunofluorescence antibody test for the detection of antibodies against Toxoplasma gondii and Neospora caninum . Results: Antibodies against PCV‐2, PRRSV, ADV, IA virus, A. pleuropneumoniae, M. hyopneumoniae, Salmonella species, Trichinella species, T. gondii and N. caninum were detected in 19.1 per cent, 12.8 per cent, 35.1 per cent, 1.1 per cent, 57.4 per cent, 0 per cent, 4.3 per cent, 6.4 per cent, 5.2 per cent and 1.1 per cent of the samples, respectively. Cluster analysis revealed a hot spot of seropositivity near Bulgarian border; seropositivity to ADV was more common among female animals. Conclusions: These results indicate exposure of wild boar to most of the above‐mentioned pathogens, raising concern about the possibility that these species may pose a significant health risk for livestock and/or humans.